Horrid Henry and the mummy's curse - Simon, Francesca (Sourcebooks, 2009)
Horrid Henry indulges in his favorite hobby--collecting Gizmos; has a bad time with his spelling homework; starts a rumor that there's a shark in the swimming pool; and spooks Perfect Peter with the mummy's curse.